Preventing hamstring injuries in sport - Brughelli, M.; Cronin, J. (Strength and Conditioning Journal, 2008)
Hamstring injuries can be devastating for athletes and sprots teams. Recent advances in technology have greatly enhanced our understanding of how and why hamstring injuries occur. Based on this information, professional sports teams have implemented various training interventions in an attempt to reduce the rate of hamstring injuries with varying success. Reviewing the recent literature on hamstring injuries and the studies that have reported decreases in injury rates could give further insight into how hamstring injruies can be orevented and this is the focus of the article.